So here are the steps to finding an inverse of a function:
Firstly, apply the first two steps:
[tex]y=\frac{3x}{x-2}\\\\x=\frac{3y}{y-2}[/tex]
Now, let's solve for y. Firstly, multiply both sides by y-2:
[tex]x(y-2)=3y\\xy-2x=3y[/tex]
Next, subtract xy on both sides:
[tex]-2x=3y-xy[/tex]
Next, factor out y on the right side of the equation:
[tex]-2x=(3-x)y[/tex]
Lastly, divide both sides by 3 - x:
[tex]-\frac{2x}{3-x}=y[/tex]
Now, apply the last step and your final answer will be [tex]-\frac{2x}{3-x}=f^{-1}(x)[/tex]